Efforts to Improve the Attitude of Glorifying Allah SWT by Submitting to His Commands in Islamic Education through the Application of the Problem Based Learning Method at SMP Negeri 10 Sibolga - Melati, Anggi; Harefa, Afnan Hariadi; Megawati (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
: This study aims to improve the Attitude of Glorifying Allah SWT in Islamic religious education learning by using the Application of the Problem Based Learning Model in. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that through the Application of the Problem Based Learning Model, it can improve the Attitude of Glorifying Allah SWT in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, through the Application of the Problem Based Learning Model can be used as an alternative to improve the Attitude of Glorifying Allah SWT in Islamic religious education learning